Surgical implications of anomalous right coronary artery from left sinus of valsalva - Bhagwan, Jai; Gupta, Anubhav; ., Sankalp; Kumar, Sudesh; Gupta, Vijay Kumar (International Surgery Journal, 2018)
Anomalous origin of right coronary artery (RCA) from left coronary sinus (LCS) can pose difficult challenge in patients undergoing cardiac surgery. Authors present a 31 years old male patient diagnosed with Rheumatic heart disease, severe mitral stenosis with moderate aortic regurgitation. Patient underwent Double valve replacement and anomalous RCA was diagnosed intraoperatively. Authors recommend that origins of coronary arteries must be echocardiographically evaluated in all patients undergoing valve surgery, especially when coronary angiography is not indicated/planned.